2014
DOI: 10.1089/ars.2013.5416
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Is Required for Acute Cardioprotection by Simvastatin

Abstract: Aims: We have shown that autophagy and mitophagy are required for preconditioning. While statin's cardioprotective effects are well known, the role of autophagy/mitophagy in statin-mediated cardioprotection is not. In this study, we used HL-1 cardiomyocytes and mice subjected to ischemia/reperfusion to elucidate the mechanism of statin-mediated cardioprotection. Results: HL-1 cardiomyocytes exposed to simvastatin for 24 h exhibited diminished protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 59 publications
(64 reference statements)
7
131
0
3
Order By: Relevance
“…Indeed, statins have been reported to decrease membrane cholesterol levels in various cell types. 35,36 Moreover, mevalonate, the cholesterol intermediate just downstream of HMG-CoA, reverses statin-induced inhibition of MTOR signaling, 37,38 indicating that HMGCR inhibition is required for the suppression of MTOR activity. However, additional studies are needed to confirm that statins reduce membrane cholesterol level in hepatocytes and that statin-induced autophagy and gluconeogenesis are mediated through the suppression of MTOR activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, statins have been reported to decrease membrane cholesterol levels in various cell types. 35,36 Moreover, mevalonate, the cholesterol intermediate just downstream of HMG-CoA, reverses statin-induced inhibition of MTOR signaling, 37,38 indicating that HMGCR inhibition is required for the suppression of MTOR activity. However, additional studies are needed to confirm that statins reduce membrane cholesterol level in hepatocytes and that statin-induced autophagy and gluconeogenesis are mediated through the suppression of MTOR activity.…”
Section: Discussionmentioning
confidence: 99%
“…The specific targeting of mitochondria for autophagic disposal during I/R insult is an important element of cardioprotection 21, 22 . Because mitochondrial autophagy is a major pathway for turnover of mitochondria, it is important to be able to monitor mitophagy.…”
Section: Methods To Measure Autophagy and Mitophagymentioning
confidence: 99%
“…They found that the cell death was prevented by cyclosporine A but not that pan-caspase inhibitor ZVAD, suggesting that the mitochondrial permeability transition pore was responsible for triggering necrotic cell death 16 . Other studies have shown the importance of clearing damaged mitochondria to reduce ischemia/reperfusion injury 2, 15, 2123 . Postconditioning was also shown to restore autophagic flux during reperfusion, whereas inhibition of flux (with chloroquine) abolished the protective effects of sevoflurane postconditioning 24 .…”
Section: Examples Of Confusing Autophagy Studies and Confounding Varimentioning
confidence: 99%
“…[18][19][20] The underlying mechanisms for these cardioprotective effects remain unclear. Given that statins induce autophagy in cancer cells, as well as in some normal cells, [21][22][23] there is reason to believe that statin-mediated cardiac benefits may be through autophagy-related mechanisms.…”
Section: Introductionmentioning
confidence: 99%